Pengembangan Modul Pembelajaran Berbasis Seni Melalui Revitalisasi Uswah Hasanah - Nova Yoga, Sahri (MADINAH, 2022)
The learning method as forming personality can be seen in the uswah hasanah method. Uswah hasanah is a learning method that is always used. The purpose of this study was to find out the development process and the effectiveness of the module with the uswah hasanah method through art-based Acehnese oral folklore revitalization. The method used in this research is research and development. The model used is the development of a 4-D model. The 4-D (Four D) development model is a learning device development model. The 4D development model consists of 4 main stages, namely: Define, Design, Develop and Disseminate. The results showed that the analysis of module validation results by Indonesian language lecturers showed an average of 3.92 which was included in the very valid category (3.5 ≤ V ≤ 4). Based on these data, it can be concluded that the module that has been developed by the researcher is suitable for use and tested on a limited scale in the field. The effectiveness of the Module using the Uswah Hasanah Method through the Revitalization of Art-Based Acehnese Oral Folklore is to conduct a limited trial on Semester I Indonesian Tadris Department students in the Literary Theory Course using the module that has been developed is very good.